2012
DOI: 10.1017/s0144686x12000244
|View full text |Cite
|
Sign up to set email alerts
|

Older people's experiences of cash-for-care schemes: evidence from the English Individual Budget pilot projects

Abstract: Cash-for-care schemes offering cash payments in place of conventional social services are becoming commonplace in developed welfare states; however, there is little evidence about the impact of such schemes on older people. This paper reports on the impact and outcomes for older people of the recent English Individual Budget (IB) pilot projects (-). It presents quantitative data on outcome measures from structured interviews with  older people who took part in a randomised controlled trial and finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 35 publications
1
73
0
Order By: Relevance
“…It is a salutary reminder that the type of 'choice and control' a person will want is not 'one size fits all'. For example, the current UK policy of offering budgetary control to older people with high support needs is not appropriate for all (Glendinning, et al, 2008;Moran et al, 2012): indeed several participants in this study found this system frightening and complex without the support of others, and felt bludgeoned into making decisions.…”
Section: Discussionmentioning
confidence: 87%
“…It is a salutary reminder that the type of 'choice and control' a person will want is not 'one size fits all'. For example, the current UK policy of offering budgetary control to older people with high support needs is not appropriate for all (Glendinning, et al, 2008;Moran et al, 2012): indeed several participants in this study found this system frightening and complex without the support of others, and felt bludgeoned into making decisions.…”
Section: Discussionmentioning
confidence: 87%
“…IBSEN's findings about IBs and older people were different from those for other user groups (people under retirement age with learning disabilities; physical disabilities or mental health problems) (see Moran et al, 2013). Older people: l Were significantly less likely than people in other user groups to report higher aspirations as a result of their experience of the IB process.…”
Section: Evidence and Evaluationsmentioning
confidence: 87%
“…Nonetheless older people generally see personal budgets as giving them more freedom of choice and control, enabling them to get support when they want it; and sometimes enabling this support to be more flexible and creative (Moran et al, 2013). They also appreciate knowing what money is available.…”
Section: The Benefits Of Personal Budgetsmentioning
confidence: 99%
“…However, in Australian community aged care the Federal Government requires the service provider to retain the CDC funds (Department of Health and Ageing, 2013). While many older people do not want the responsibility of organising their support and managing their budget (Moran et al, 2013), some individuals or their representatives are lobbying for this possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Greater flexibility and choice can result in more opportunities for abuse and exploitation, although few instances have been reported or observed (Glendinning et al, 2008;Manthorpe & Samsi, 2013). Additional tensions result because case managers no longer have pooled funds to draw upon if funding is insufficient to meet an individual's needs (Moran et al, 2013).…”
Section: Introductionmentioning
confidence: 99%